2012
DOI: 10.1038/ijos.2012.35
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear finite element analysis of three implant–abutment interface designs

Abstract: The objective of this study was to investigate the mechanical characteristics of implant–abutment interface design in a dental implant system, using nonlinear finite element analysis (FEA) method. This finite element simulation study was applied on three commonly used commercial dental implant systems: model I, the reduced-diameter 3i implant system (West Palm Beach, FL, USA) with a hex and a 12-point double internal hexagonal connection; model II, the Semados implant system (Bego, Bremen, Germany) with combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 24 publications
3
42
0
3
Order By: Relevance
“…Young's Modulus and Poisson's Ratio of cortical and cancellous bone are determined in respect to previous FEA studies [3][4][5].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Young's Modulus and Poisson's Ratio of cortical and cancellous bone are determined in respect to previous FEA studies [3][4][5].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…The results of these simulations may provide information that clinically is not yet available, reducing the time and repetitive clinical experiences (Tang et al 2012). However, in certain conditions, due to the great complexity of the systems, there is a need for simplification, which should not interfere with the results of the FEA.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Tang et al showed that 12-point double hexagon con nection had better stress distribution and produced smaller displacement compared to other designs. 9 …”
Section: Twelve-point Hexagonmentioning
confidence: 99%